2021
DOI: 10.3389/fphar.2021.712489
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Inhibition of Mitochondrial Fission on Organ Function After Sepsis

Abstract: Sepsis-associated organ dysfunction plays a critical role in its high mortality, mainly in connection with mitochondrial dysfunction. Whether the inhibition of mitochondrial fission is beneficial to sepsis-related organ dysfunction and underlying mechanisms are unknown. Cecal ligation and puncture induced sepsis in rats and dynamic related protein 1 knockout mice, lipopolysaccharide-treated vascular smooth muscle cells and cardiomyocytes, were used to explore the effects of inhibition of mitochondrial fission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The sodium pentobarbital (45 mg/kg, i. p.) was used for anesthetizing rats for the surgical procedure. The cecal ligation and puncture (CLP) was applied to reproduce systemic inflammatory response as described previously ( Zhu et al, 2021 ). Briefly, the cecum was exposed carefully and ligated and punctured 0.7 cm from a distance with a triangular needle 1.5 mm in diameter, and fecal matter was allowed to flow into the abdominal cavity freely.…”
Section: Methodsmentioning
confidence: 99%
“…The sodium pentobarbital (45 mg/kg, i. p.) was used for anesthetizing rats for the surgical procedure. The cecal ligation and puncture (CLP) was applied to reproduce systemic inflammatory response as described previously ( Zhu et al, 2021 ). Briefly, the cecum was exposed carefully and ligated and punctured 0.7 cm from a distance with a triangular needle 1.5 mm in diameter, and fecal matter was allowed to flow into the abdominal cavity freely.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in a rat model of ischemia, Mdivi-1 increased Δψ and the authors attribute this behavior to the regulatory action of the reagent on mitophagy mediated by PINK/Parking proteins [ 56 ]. It was also shown in LPS-exposed cardiomyocytes that Mdivi-1 contributes to the recovery of Δψ [ 57 ]. The effects of Mdivi-1 on the Δψ regulation would be related to mitochondrial membrane integrity maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Our previous study found that inhibition of mitochondrial fission could decrease the mortality of sepsis, protect vital organ functions, including cardiovascular function, liver, kidney, and intestinal function. [14] Moreover, inhibition of mitochondrial over-fission could enhance tissue perfusion, oxygen supply and oxygen consumption. Present study demonstrated that inhibition of mitochondrial over-fission was beneficial to early treatment of hemorrhagic shock in hot environment that could prolong golden treatment time and protect organ function.…”
Section: Discussionmentioning
confidence: 99%
“…The studies confirmed that Mdivi-1 could protect the functions of heart, nerves and other organs by inhibiting mitochondrial division. [12][13][14] Whether Mdivi-1 is suitable for the early treatment of hemorrhagic shock in hot environment by inhibiting mitochondrial division is not known.…”
Section: Introductionmentioning
confidence: 99%